2016
DOI: 10.1371/journal.pone.0150945
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocytes Traffic into the Brain across the Blood-CSF Barrier: Evidence Using a Reconstituted Choroid Plexus Epithelium

Abstract: An emerging concept of normal brain immune surveillance proposes that recently and moderately activated central memory T lymphocytes enter the central nervous system (CNS) directly into the cerebrospinal fluid (CSF) via the choroid plexus. Within the CSF space, T cells inspect the CNS environment for cognate antigens. This gate of entry into the CNS could also prevail at the initial stage of neuroinflammatory processes. To actually demonstrate T cell migration across the choroidal epithelium forming the blood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Another study found only a marginal increase in T cells in the stroma [129], that can be interpreted as the choroid plexuses being gateway to the CSF during EAE rather than sites of accumulation per se. On the other hand in vitro studies employing inverse configurations of the BCSFB have provided solid evidence for the migration of activated T cells from the basolateral to apical site of choroid plexus epithelial cells in response to CSF derived factors such as CXCL12 [77,147]. These observations raise the question if there is an alternative route for T-cell entry into the CNS from the choroid plexus stroma.…”
Section: Neuroimmune Function Of the Choroid Plexuses In Neurologicalmentioning
confidence: 99%
“…Another study found only a marginal increase in T cells in the stroma [129], that can be interpreted as the choroid plexuses being gateway to the CSF during EAE rather than sites of accumulation per se. On the other hand in vitro studies employing inverse configurations of the BCSFB have provided solid evidence for the migration of activated T cells from the basolateral to apical site of choroid plexus epithelial cells in response to CSF derived factors such as CXCL12 [77,147]. These observations raise the question if there is an alternative route for T-cell entry into the CNS from the choroid plexus stroma.…”
Section: Neuroimmune Function Of the Choroid Plexuses In Neurologicalmentioning
confidence: 99%
“…They are not the only immune cell in the brain. Other immune cell types include, but are not limited to, macrophages and lymphocytes (Strazielle et al 2016). Perivascular, meningeal, and choroid plexus macrophages also reside at the CNS interface (Goldmann et al 2016).…”
Section: Role Of Microgliamentioning
confidence: 99%
“…SELPLG and CORO1C ) and their immunohistochemically strongly expressed protein products (selectin‐P ligand and coronin‐1C) have been given a pathogenetic role, given the role of these proteins in cell migration‐chemotaxis and cell motility, respectively. P‐selectin is expressed selectively by choroid plexus and meningeal vessels, and the expression of its ligand could explain access of neoplastic cells from the circulation into the CSF, as has been proven for T‐lymphocytes during normal brain immune surveillance . Involvement of CSF in some of the previously reported cases in which cerebral masses were present can be attributed simply to direct extension from involved superficial brain parenchyma.…”
Section: Discussionmentioning
confidence: 94%
“…Pselectin is expressed selectively by choroid plexus and meningeal vessels, and the expression of its ligand could explain access of neoplastic cells from the circulation into the CSF, as has been proven for T-lymphocytes during normal brain immune surveillance. 43 Involvement of CSF in some of the previously reported cases in which cerebral masses were present 3,4 can be attributed simply to direct extension from involved superficial brain parenchyma. The lymph node involvement in our case lends support to the recently described finding (mostly in animal models, but also in humans) of a lymphatic connection between CSF and deep cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 96%